Topical imiquimod before intradermal trivalent influenza vaccine for protection against heterologous non-vaccine and antigenically drifted viruses: a single-centre, double-blind, randomised, controlled phase 2b/3 trial. Issue 2 (February 2016) - Hung, Ivan Fan-Ngai; Zhang, Anna Jinxia; To, Kelvin Kai-Wang; Chan, Jasper Fuk-Woo; Li, Patrick; Wong, Tin-Lun; Zhang, Ricky; Chan, Tuen-Ching; Chan, Brian Chun-Yuan; Wai, Harrison Ho; Chan, Lok-Wun; Fong, Hugo Pak-Yiu; et al.
Summary: Background: Pretreatment with topical imiquimod, a synthetic agonist of toll-like receptor 7, significantly improved the immunogenicity of influenza vaccination in elderly people. We aimed to clarify its effect in a younger age group. Methods: In this double-blind, randomised controlled trial, we enrolled healthy volunteers aged 18–30 years in early 2014 to receive the 2013–14 northern-hemisphere winter trivalent influenza vaccine at the Queen Mary Hospital, (Hong Kong, China). Eligible participants were randomly assigned (1:1:1:1) to one of the four vaccination groups: the study group, topical imiquimod-cream followed by intradermal trivalent influenza vaccine (INF-Q-ID), or one of three control groups, topical aqueous-cream control followed by intradermal trivalent influenza vaccine (INF-C-ID), topical aqueous-cream control followed by intramuscular trivalent influenza vaccine (INF-C-IM), and topical imiquimod-cream followed by intradermal normal-saline injection (SAL-Q-ID). Randomisation was by computer-generated lists in blocks of four. The type of topical treatment was masked from volunteers and investigators, although not from the study nurse. Serum haemagglutination-inhibition and microneutralisation-antibody titres were assayed. The primary outcome was seroconversion at day 7 after treatment for three vaccine strains of influenza (A/California/07/2009 H1N1-like virus [A/California/H1N1], A/Victoria/361/2011 H3N2-like virus [A/Victoria/H3N2], and B/Massachusetts/2/2012-like virus [B/Yamagata lineage]) and four non-vaccine strains (A/HK/485197/14 [H3N2 Switzerland-like lineage], prototype A/WSN/1933 [H1N1], A/HK/408027/09 [prepandemic seasonal H1N1], and B/HK/418078/11 [Victoria lineage]). Analysis was done on an intention-to-treat basis. This trial is registered withClinicalTrials.gov, numberNCT02103023 . Findings: We enrolled 160 healthy volunteers between March 1 and May 31, 2014, and 40 participants were randomly assigned to each study group. For the A/California/H1N1 strain, seroconversion at day 7 occurred in 39 participants (98%) in the INF-Q-ID group, 25 (63%) in the INF-C-ID group, 18 (45%) in the INF-C-IM group, and none in the SAL-Q-ID group; for the A/Victoria/H3N2, this was 30 (75%) in the INF-Q-ID group, four (10%) in the INF-C-ID group, four (10%) in the INF-C-IM group, and none in the SAL-Q-ID group; and for the B/Massachusetts (Yamagata lineage) strain, this was 36 (90%) in the INF-Q-ID group, 27 (68%) in the INF-C-ID group, 17 (43%) in the INF-C-IM group, and one (3%) in the SAL-Q-ID group (p<0·0001 for all three vaccine strains). Adverse reactions were infrequent and self-limited and did not differ between the four groups. Furthermore, the seroconversion rate against the four non-vaccine strains was better in the INF-Q-ID group than in the control groups on days 7 and 21 (p<0·0001). The most common adverse events were grade 1 redness (five participants in the INF-Q-ID group, three in INF-C-ID, one in INF-C-IM, and one in SAL-Q-ID) and grade 1 swelling (seven participants in INF-Q-ID group, five in INF-C-ID, three in INF-C-IM, and two in SAL-Q-ID. Interpretation: Topical application of imiquimod before intradermal trivalent influenza vaccine significantly improved immunogenicity against the vaccine influenza strains in young healthy individuals and increased immunogenicity against the non-vaccine strains, especially the antigenically drifted H3N2 strain of 2015, which was not included in the 2013–14 recommended vaccine. Further studies should be done to establish the efficacy and safety of this approach for other injectable vaccines to augment the onset and range of protection. Funding: The Shaw Foundation Hong Kong, Health and Medical Research Fund (Hong Kong, China), The Consultancy Service for Enhancing Laboratory Surveillance of Emerging Infectious Disease for the HKSAR (Department of Health, Hong Kong, China), The Providence Foundation, Respiratory Viral Research Foundation.